Impact of defocus incorporated multiple segments (DIMS) spectacle lenses for myopia control on quality of life of the children: a qualitative study - Sumita Agarkar; Anuradha Narayanan; Mobashir Fatimah (BMJ Open Ophthalmology)
Objective To assess the impact of DIMS (defocus incorporated multiple segments) spectacle lenses on the quality of life of children using it.Methods Separate in-depth interviews were conducted with children using DIMS as a myopia control strategy for at least 1 month and their parents based on prepared guides. The recorded audio of the interviews was transcribed, and the significant data points were coded using a hybrid approach, that is, both the inductive and deductive coding methods were used to identify themes. The generated codes were further grouped, categorised and finally fitted as per relevance into the subdomains of the four domains of the WHO Quality of Life—Brief framework, namely the domains of social relationships, physical, psychological and environmental health.Results A total of 29 interviews were conducted, 15 with children (mean age: 12.47±2.13 years) and 14 with parents. Thematic analysis was done and a total of 63 codes were generated with 2, 16, 17 and 28 codes aligning to the domains of social relationships, environmental, psychological and physical health, respectively. Most parents did not notice any change in their child’s visual behaviour, yet children did experience symptoms such as peripheral blurred vision, eyestrain, headache, haloes and more during the adaptation period. High-cost, scratch-prone nature and difficulty in procurement were a few concerns raised by parents.Conclusions Participants were satisfied with most of the facets of social relationships, physical and psychological health domains. However, a few facets such as quality, accessibility and finance of the environmental health domain need improvement.